2022
DOI: 10.3389/fpubh.2022.920355
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Determinants of Prenatal Breastfeeding Knowledge, Attitude, and Intention Among Pregnant Women: A Cross-Sectional Study in Northwest Ethiopia

Abstract: BackgroundPregnant women are a critical part of the community to assess various determinants of their future breastfeeding practice. This study aimed to assess the levels and determinants of breastfeeding knowledge, attitude, and intention among pregnant women.MethodsA hospital-based cross-sectional study was conducted among 422 pregnant women from January 18 to February 27, 2022, at Debre Tabor Comprehensive Specialized Hospital (DTCSH) in Northwest Ethiopia. Data were collected via face-to-face interviews fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Studies have shown that multiparous pregnants have significantly higher breastfeeding knowledge and tendencies than nulliparous pregnants [2]. In our study, mothers with two or more children breastfeed their children longer than mothers with one child.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Studies have shown that multiparous pregnants have significantly higher breastfeeding knowledge and tendencies than nulliparous pregnants [2]. In our study, mothers with two or more children breastfeed their children longer than mothers with one child.…”
Section: Discussionsupporting
confidence: 41%
“…Although breastfeeding is a feeding method as old as human history, effective breastfeeding is not practiced sufficiently in many countries [2]. !…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge is well documented in previous national [ 31 , 32 ] and international studies [ 17 , 33 , 34 ] to be strongly linked to satisfactory EBF practices. The link between breastfeeding knowledge and satisfactory EBF practices seems logical because if the woman has to adopt any behavior, she should have sufficient knowledge to fit in and gain harmony with her previous mental schema.…”
Section: Discussionmentioning
confidence: 88%
“…where n is the sample size; Z1 − α/2 is the standard normal variable, at 95% confidence degree = 1.96; P is the anticipated proportion of pregnant women intended to breastfeed (P = 65.4%) from previous research [19]; and d is the margin of error = 0.05. The result of the sample size calculation equals 382 after the addition of 15% to anticipate the low response rate.…”
Section: Sample Size Determinations and Sampling Proceduresmentioning
confidence: 99%